Evaluation of clinical pharmacy priority scoring methods in an adult medicine residency clinic. Issue 6 (23rd April 2019) - Krasniak, Anne; Szymaniak, Gregory; Conn, Kelly M.; Phillips, Elizabeth
Abstract : Background: Patients with higher clinical pharmacy priority (CP2) scores are more likely to receive a medication recommendation from a pharmacist to resolve an identified medication related problem (MRP) in a family medicine clinic. Objective: The objective of this study was to compare a modified CP2 score to the original CP2 score in an adult medicine residency clinic and assess whether a modified CP2 score more appropriately captured patients in need of recommendations from a clinical pharmacist. Methods: A convenience sample of patients scheduled for visits in an adult medicine clinic had a comprehensive medication review (CMR) performed. All patients had the original CP2 score and modified CP2 score calculated retrospectively. Both versions of the CP2 scores were compared using Pearson correlation. The relationship between a recommendation from a pharmacist and each CP2 score was evaluated using Pearson correlation and t test. Results: In total, 148 patients who received a CMR by a clinical pharmacist were included in the retrospective chart review. Overall, there was a strong positive correlation between the CP2 score and the modified CP2 score (correlation coefficient ( r ) 0.968, P < 0.001); thus, as the CP2 scores increase, the modified CP2 score increases. Patients with higher CP2 and modified CP2 scores were more likely to receive a recommendation from a pharmacist ( P < 0.001 and P < 0.001, respectively). There was a moderate correlation between both scores and number of recommendations made (CP2: r = 0.436 [ P < 0.001], modified CP2: r = 0.456 [ P < 0.001]) which did not differ significantly. Conclusions: The CP2 score and the modified CP2 score were both associated with pharmacist recommendations in an adult medicine clinic. Refinement of the CP2 score did not better capture patients in an adult medicine residency clinic with a recommendation from a clinical pharmacist.